Contraceptive Method Mix and HIV Risk Behaviors Among Kenyan Adolescent Girls and Young Women Seeking Family Planning Services: Implications for Integrating HIV Prevention - Nyaboe, Edward; Larsen, Anna; Sila, Joseph; Kinuthia, John; Owiti, George; Abuna, Felix; Kohler, Pamela; John-Stewart, Grace; Pintye, Jillian (Frontiers in Reproductive Health, 2021)
Background: Understanding HIV risk behaviors among adolescent girls and young women (AGYW) seeking contraception could help inform integrating HIV prevention services within family planning (FP) clinics. Methods: From 10/2018 to 04/2019, we conducted a survey at 4 FP clinics in Kisumu, Kenya to evaluate risk behaviors among AGYW without HIV infection seeking contraception. All AGYW aged 15–24 were invited to participate following receipt of FP services. Adolescent girls and young women initiating or refilling contraception were included in this analysis. Long-acting reversible contraceptives (LARC) included intrauterine devices, implants, or injectables. Non-LARC methods included oral contraceptive pills (OCP) or condoms. We used an empiric risk score to assess HIV risk behaviors; HIV risk scores of ≥5 (corresponding to 5–15% HIV incidence) defined “high” HIV risk. Results: Overall, 555 AGYW seeking FP were included. Median age was 22 years [interquartile range (IQR) 20–23], median completed education was 12 years (IQR 10–12); 23% of AGYW had HIV risk scores of ≥5. The most frequent form of contraception was injectables (43%), followed by implants (39%). After adjustment for education, prior pregnancy, and marital status, LARC users more frequently engaged in transactional sex than non-LARC users [6 vs. 0%, adjusted prevalence ratio (PR) = 1.17, 95% CI 1.09–1.29, p < 0.001]; LARC use was not associated with HIV risk scores ≥5. Among LARC users, AGYW using injectables more frequently had condomless sex compared to AGYW using other LARC methods (85 vs. 75%, adjusted PR = 1.52, 95% CI 1.09–2.10, p = 0.012); injectable use was not associated with HIV risk scores ≥5. Conclusions: Adolescent girls and young women seeking contraception frequently had high HIV risk, emphasizing the importance of integrating HIV prevention within FP. Multipurpose technologies for contraception and HIV prevention could particularly benefit AGYW.